The estimation of pork carcass primal cuts value based on backfat thickness - Kamil Duziński; Dariusz Lisiak; Damian Knecht; Sebastian Środoń (Journal of Central European Agriculture, 2015)
The aim of the present study was to determine the effect of pork carcass backfat thickness on the dissection efficiency of four primal cuts (ham, loin, shoulder, belly), including correlation coefficients. The research material consisted of 80 pork carcasses. Backfat thickness (mm) was measured on cold half-carcasses using a vernier caliper at 6 points: at the first cervical vertebra (atlas), over shoulder at the thickest point, on the back, at the beginning, center, end of the gluteus medius muscle (CI, CII, CIII). On the basis of the average backfat thickness, measurements from 6 points were separated into two experimental groups: I (<25 mm); II (≥25 mm). Detailed dissection of the elements was performed to define mass (g): total, intermuscular fat, bones and lean meat. The significant effect of fat thickness on intermuscular fat content regardless of the cut was noted. Correlations between the average backfat thickness of 6 points and the total weight of the four main elements were calculated. In addition, the correlation coefficients were compared between the dissection elements and the average backfat thickness of 6 and 5 points. Higher backfat thickness determined the increase in the total mass of loin, shoulder and belly. A statistically proven correlation was shown between the average backfat thickness and the total mass of the analysed elements (r=0.293). When comparing the correlation coefficients of a different number of measurements a specific tendency was observed. Positive correlation coefficients were slightly higher for an average of 5 points of backfat thickness and negative correlation coefficients were slightly higher for an average of 6 points. Statistical differences between groups were recorded at the same level for the same parameters (P≤0.001 and 0.01<P≤0.05). The average backfat thickness of 6 points can be used as an indicator of the amount and quality of pork carcass primal cuts, with no adverse effects compared to standard 5 points.